Analysis of spectrum allocation of secondary users based on linear cooperative spectrum sensing techniques in cognitive radio networks - Zachary Bosire Omariba (Trends in Computer Science and Information Technology - Peertechz Publications, 2021)
This study is based on using the optimization problem of linear cooperative spectrum sensing (CSS) techniques for the analysis and correlation of spectrum allocation to secondary users (SUs) without interfering with the operations of the primary users. To achieve this the system must discover when the licensed users are not using their assigned spectrum so that the spectrum is assigned to the unlicensed users. But when the PUs surfaces the Sus that is holding the spectrum releases it immediately. The probabilities of detection, probability of false alarm, and probability of miss detection msust be kept as low as possible and this is confirmed in our simulation results which indicates that probabilities is kept at <1. This indicates that there is improved spectrum efficiency in CSS where the SUs uses the spectrum without interfering with the PUs thus forming the main objective of cooperative spectrum sensing.